External sources of techonological innovation in Chilean manufacturating industry - Alvarez, Roberto (Estudios de Economía, 2016)
There are several arguments in the literature regarding that more open economieswould grow faster in the long term. Nevertheless, the channels through whichopenness increases growth have not been clearly identified in empirical analysis.In this article, we study if outward orientation variables have a positive impacton technological innovation, which is one of the most important sources of productivitygrowth. Using microeconomic data for Chilean manufacturing industry,we identify the effect of three main mechanisms of technological absorption:exports, direct foreign investment and purchase of foreign technical licenses. Theresults suggest that exports increase significantly technological innovation. Inaddition, we found causality in both ways. Technological innovation increasesthe probability of exporting. The other two channels; direct foreign investmentand technical licenses, would be less important, because they only affect a reducednumber of technological innovation indicators.